Production of methane from palm oil mill effluent by using iltrasonicated membrane anaerobic system (UMAS) - Wai Mun, Yap (2012)
The direct discharge of the Palm Oil Mill Effluent (POME) wastewater causes serious environmental pollution due to its high chemical oxygen demand (COD), total suspended solids (TSS) and biological oxygen demand (BOD). The conventional ways for POME wastewater treatment have both economical and environmental disadvantages. In this study, the potential of ultrasonic-assisted membrane anaerobic system (UMAS) was evaluated as alternative and cost effective method for treating POME wastewater to avoid fouling. Throughout the experiment, the removal efficiency of COD was 95% with HRT of 6 days. The BOD removal efficiency was 74% while TSS removal rate was from 91 to 99.5%.The methane gas production efficiency was 82.14%.The UMAS treatment efficiency was greatly improved by UMAS introduction. The membrane fouling and polarization at the membrane surface was significantly reduced.